Renormalized Flory‐Huggins lattice model of physicochemical kinetics and dynamic complexity in self‐healing double‐network hydrogel - Mokarram Hossain (Journal of Applied Polymer Science, 2021)
Self‐healing capability offers great designability on mechanical properties of double‐network (DN) hydrogel. However, the thermodynamics understanding behind such physicochemical transitions and self‐healing behaviors are yet to be explored properly. This study describes a renormalized Flory‐Huggins lattice model for DN hydrogels, of which the physicochemical kinetics and dynamic complexity are resulted from stress‐induced bond scission and macromolecule rearrangement. Based on the Flory‐Huggins lattice model and Gaussian distribution theory, an extended free‐energy model was formulated by the steric repulsive free‐energy function. Afterwards, the function was used to identify the working mechanisms and thermodynamics in self‐healing DN hydrogels with ultra‐high mechanical strength. Finally, the effectiveness of model was demonstrated by applying it to predict the mechanical behaviors of DN hydrogels, where the analytical results showed good agreements with experiment data.